2021
DOI: 10.1186/s12974-021-02349-y
|View full text |Cite
|
Sign up to set email alerts
|

p38-TFEB pathways promote microglia activation through inhibiting CMA-mediated NLRP3 degradation in Parkinson's disease

Abstract: Background Parkinson’s disease (PD) is characterized by degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNpc), accompanied by accumulation of α-synuclein, chronic neuroinflammation and autophagy dysfunction. Previous studies suggested that misfolded α-synuclein induces the inflammatory response and autophagy dysfunction in microglial cells. The NLRP3 inflammasome signaling pathway plays a crucial role in the neuroinflammatory process in the central nervous system. Ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 44 publications
(38 reference statements)
0
40
0
Order By: Relevance
“…MAP kinases are important contributors to pain sensitization after nerve injury [ 49 ]. A potential interaction between MAP kinase signaling and αSyn has already been described, with overexpression of αSyn associated with upregulation of p38 and p42/44 activity [ 50 , 51 , 52 ]. In addition, inhibition of p38 was linked to protective effects in PD and to a decrease in microglia activation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAP kinases are important contributors to pain sensitization after nerve injury [ 49 ]. A potential interaction between MAP kinase signaling and αSyn has already been described, with overexpression of αSyn associated with upregulation of p38 and p42/44 activity [ 50 , 51 , 52 ]. In addition, inhibition of p38 was linked to protective effects in PD and to a decrease in microglia activation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A potential interaction between MAP kinase signaling and αSyn has already been described, with overexpression of αSyn associated with upregulation of p38 and p42/44 activity [ 50 , 51 , 52 ]. In addition, inhibition of p38 was linked to protective effects in PD and to a decrease in microglia activation [ 51 ]. Therefore, downregulation of MAPK activation in Snca knock-out mice after nerve injury associated with decreased mechanical allodynia in our study fits very well with the already published data.…”
Section: Discussionmentioning
confidence: 99%
“…The microglia possess an immune function and secrete pro-inflammatory cytokines. According to the functions of microglia in the neuroinflammation, they can be categorized into two groups: poisonous to nerves (M1-phenotype microglia) and protective to nerves (M2-phenotype microglia) (Biondetti et al, 2021;Chen et al, 2021). Activated microglia secrete interleukin-1α (IL-1α), tumor necrosis-α (TNF-α), and C1q, the first subcomponent of the C1 complex, which induce astroglia into A1s (Cheng et al, 2021).…”
Section: Gliamentioning
confidence: 99%
“…In addition, lysozyme 2Cre (Lyz2cre)-mediated deletion of microglial autophagy-related gene 5 (ATG5) aggravates neuroinflammation and loss of dopaminergic neurons in the substantia nigra and aggravates the loss of α-synuclein overexpressing mice ( Tu et al, 2021 ). In addition, α-Syn leads to microglial activation by activating TLR4 and its downstream p38 and Akt-mTOR signaling ( Chen et al, 2021 ). Miki et al (2018) found that the autophagy core regulator genes ULK3, Atg2A, Atg4B, Atg5, Atg16L1, and histone deacetylase six mRNAs were downregulated when they studied the peripheral blood mononuclear and cell-based autophagy of Parkinson’s patients, and the autophagy protein ULK1 was downregulated, Beclin1 protein levels were significantly increased, and the mRNA expression of these proteins was negative feedback and correlated with increased α-synuclein levels.…”
Section: Interaction Between Autophagy and Nlrp3 Inflammasome In Neur...mentioning
confidence: 99%